Development of Puter Ice Cream Maker Based on Appropriate Technology to Increase Small Business Productivity in Manggis Village: Pengembangan Alat Pembuat Es Krim Puter Berbasis Teknologi Tepat Guna untuk Meningkatkan Produktivitas Usaha Kecil di Desa Manggis - Mulyadi, Akhmad; Aisidah, Suffi Natul; Fatima, Siti; Haqewi, Muhammad Danil (Proceedings of The ICECRS, 2025)
General Background: Appropriate technology plays a crucial role in supporting small-scale businesses, particularly in rural areas where access to electricity and advanced machinery is limited. Specific Background: Ice cream production often relies on electric-powered machines, which may not be feasible for micro-enterprises operating with minimal resources. Knowledge Gap: There is a lack of accessible, energy-independent tools that maintain product quality while meeting the operational needs of small food entrepreneurs. Aims: This study aims to develop a manually operated ice cream maker that is simple, cost-effective, and energy-efficient to support the productivity of small-scale businesses. Results: The research involved the design and fabrication of a hand-cranked ice cream maker, followed by performance testing based on production time and product quality. The results indicate that the device can produce ice cream within 15–20 minutes, yielding texture and taste comparable to commercially available ice cream. Novelty: The innovation lies in creating an efficient, electricity-free production tool tailored to the constraints of rural enterprises, thereby enabling consistent product output without reliance on external power sources. Implications: This tool offers a sustainable solution for small business owners by reducing production costs, increasing operational flexibility, and supporting local economic development. It demonstrates how appropriate technology can serve as a catalyst for entrepreneurship in underserved areas, with the potential for wider application in the food processing sector. Keywords: Appropriate Technology, Hand-Cranked Ice Cream Maker, Small-Scale Business, Rural Innovation, Energy-Efficient Tools Highlights: Manual ice cream maker operates without electricity and maintains quality. Design supports rural entrepreneurs with limited access to resources. Innovation reduces costs while boosting local business productivity.